2018
DOI: 10.1038/s41598-018-31184-0
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Antisolvent Ambient Processed Large Grain Size Perovskite Thin Films for High-Performance Solar Cells

Abstract: In recent years, hybrid organic-inorganic halide perovskites have been widely studied for the low-cost fabrication of a wide range of optoelectronic devices, including impressive perovskite-based solar cells. Amongst the key factors influencing the performance of these devices, recent efforts have focused on tailoring the granularity and microstructure of the perovskite films. Albeit, a cost-effective technique allowing to carefully control their microstructure in ambient environmental conditions has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 72 publications
2
99
0
Order By: Relevance
“…At the same time, part of organic components (e.g., methylammonium iodide (MAI)) in perovskite precursors tends to evaporate rather than form a perovskite phase during annealing procedure, due to the high volatility and instability of MAI, thus the perovskite evolves into PbI 2 and loses its excellent photovoltaic properties over time 28–32. This tangled problem can be partially mitigated by using mixed‐(anti)solvent system to regulate perovskite films growth dynamic, such as CB/isopropyl alcohol,33 CB/ethanol,34 CB/acetonitrile,35 and EA/hexane 36. These studies found that the percentage and solubility of additive solvents in mixed‐(anti)solvent system contribute to manipulate the morphology of the perovskite active layers 34.…”
Section: Photovoltaic Performance Of Champion Pscs Based On Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, part of organic components (e.g., methylammonium iodide (MAI)) in perovskite precursors tends to evaporate rather than form a perovskite phase during annealing procedure, due to the high volatility and instability of MAI, thus the perovskite evolves into PbI 2 and loses its excellent photovoltaic properties over time 28–32. This tangled problem can be partially mitigated by using mixed‐(anti)solvent system to regulate perovskite films growth dynamic, such as CB/isopropyl alcohol,33 CB/ethanol,34 CB/acetonitrile,35 and EA/hexane 36. These studies found that the percentage and solubility of additive solvents in mixed‐(anti)solvent system contribute to manipulate the morphology of the perovskite active layers 34.…”
Section: Photovoltaic Performance Of Champion Pscs Based On Differentmentioning
confidence: 99%
“…This tangled problem can be partially mitigated by using mixed‐(anti)solvent system to regulate perovskite films growth dynamic, such as CB/isopropyl alcohol,33 CB/ethanol,34 CB/acetonitrile,35 and EA/hexane 36. These studies found that the percentage and solubility of additive solvents in mixed‐(anti)solvent system contribute to manipulate the morphology of the perovskite active layers 34. However, it is a challenge to optimize the formulation of mixed‐(anti)solvent systems which greatly increases the time cost.…”
Section: Photovoltaic Performance Of Champion Pscs Based On Differentmentioning
confidence: 99%
“…However, the grains in the modified films are larger and with the same dimension of the thickness. We believe that the chloroform solvent promoted a slightly superficial dissolution of the perovskite film, allowing the surfactant to reorganize and form the 2D structures . This is an indication of a total penetration of the surfactant solution into the perovskite film.…”
Section: Resultsmentioning
confidence: 89%
“…Through this method, they similarly observed as previously, larger perovskite crystallites at higher %RH with reduced grain boundaries and hysteretic behaviour that they attributed to a decrease in traps states. [52] In their case, (Figure 4c) a combination of ethanol (EtOH) and chlorobenzene (CB) in various volumetric proportions is revealed as the crucial protagonist avoiding pin-holes and obtaining controllable size of perovskite grains, improving as well the photovoltaic parameters to achieve PCE up to 14 % in a planar configuration. [51] In their work, methanol is used as an additive onto the diethylether antisolvent to remove the residual water occluded in the perovskite material during first steps of crystallization (Figure 4b).…”
Section: Effect Of H 2 O As Moisture In Ambient Atmospherementioning
confidence: 99%